2007
DOI: 10.1002/ijc.22667
|View full text |Cite
|
Sign up to set email alerts
|

Six‐month natural history of oral versus cervical human papillomavirus infection

Abstract: Human papillomavirus (HPV) infection is etiologically associated with a subset of oral cancers, and yet, the natural history of oral HPV infection remains unexplored. The feasibility of studying oral HPV natural history was evaluated by collecting oral rinse samples on 2 occasions at a 6-month interval from 136 HIV-positive and 63 HIV-negative participants. Cervical vaginal lavage samples were concurrently collected for comparison. HPV genomic DNA was detected in oral and cervical samples by consensus primer P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
138
10
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 157 publications
(168 citation statements)
references
References 40 publications
16
138
10
4
Order By: Relevance
“…The current knowledge about the natural history of oral HPV infection come from gynaecological literature about cervical infection, although, as recently suggested by D'Souza et al [34], oral and genital HPV infection seem to differ themselves about some aspects.…”
Section: Natural History Of Hpv Infectionmentioning
confidence: 99%
“…The current knowledge about the natural history of oral HPV infection come from gynaecological literature about cervical infection, although, as recently suggested by D'Souza et al [34], oral and genital HPV infection seem to differ themselves about some aspects.…”
Section: Natural History Of Hpv Infectionmentioning
confidence: 99%
“…Risk factors for oral HPV infection include smoking and sexual behaviors as well as demographic characteristics (2)(3)(4). Moreover, immunosuppressed individuals are at an increased risk of oral HPV infection (5). Although HPV is sexually transmitted and several large studies have found a strong association with oral sexual behaviors (2,4,6), some studies have failed to find this association (3,7).…”
Section: Introductionmentioning
confidence: 99%
“…For these types of tumors, HPV 16 is the most common virus [9]. Also, tumors in tongue, trough [11], and tonsil are also caused by HPV [10]. Similar to most neoplasias, tumor development is a progressive disease.…”
Section: Prophylactic and Therapeutic Vaccines Against Human Papillommentioning
confidence: 99%